Characterization of volatile compounds profiles and identification of key volatile and odor-active compounds in 40 sweetpotato (Ipomoea Batatas L.) varieties - Rong Zhang; Chaochen Tang; Bingzhi Jiang; Xueying Mo; Zhangying Wang (Food Chemistry: X)
Sweetpotato with different flesh colors exhibits significant differences in flavor. Nevertheless, research on the identification of the key aromatic compounds in sweetpotato is scarce. Therefore, 40 primary sweetpotato varieties with different flesh colors were analyzed by HS-SPME/GC–MS to characterize the volatile compounds. A total of 121 volatile compounds were detected, with aldehydes, furans and terpenes being the most abundant components. Additionally, 35 compounds were identified as the key aromatic compounds by OAV > 1, of which 17 were found in all varieties and hence considered as the major components of sweetpotato aroma. Further analysis demonstrated that the yellow-fleshed sweetpotato had the strongest aroma, which was presumed due to the aldehydes like (E,E)-2,4-heptadienal, nonanal, (E,E)-2,4-decadienal,etc. that were produced during the degradation of unsaturated fatty acids. The unique sweety and floral aroma of orange-fleshed sweetpotato might be attributed to apocarotenoid volatiles (trans-beta-ionone, β-ionone, geranylacetone, etc.), the derivates of carotenoids. The purple-fleshed sweetpotato exhibited weak aroma with a significantly high terpenoids concentration. Overall, these findings may be the main reason for the different aromas of different colored sweetpotatoes and provides insights into sweetpotato aroma and a theoretical basis for improving sweetpotato aroma.